2008
DOI: 10.1164/rccm.200711-1661oc
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Proteins A and D Suppress Alveolar Macrophage Phagocytosis via Interaction with SIRPα

Abstract: Rationale: Efficient removal of apoptotic cells is essential for the resolution of acute pulmonary inflammation. Alveolar macrophages ingest apoptotic cells less avidly than other professional phagocytes at rest but overcome this defect during acute inflammation. Surfactant protein (SP)-A and SP-D are potent modulators of macrophage function and may suppress clearance of apoptotic cells through activation of the transmembrane receptor signal inhibitory regulatory protein a (SIRPa). Objectives: To investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
172
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 52 publications
10
172
0
Order By: Relevance
“…We report that rno-miR-3585-5p negatively alters two genes; BAZ2A and SIRPA; however, the exact mechanism is poorly understood. It has been shown that SIRPA, a member of the signalregulatory-protein family, can interact with surfactant proteins A and D to suppress alveolar phagocytosis without triggering an inflammatory response (41). This protein can be phosphorylated by tyrosine kinases and is found to participate in signal transduction triggered by CD47 and mediated by various growth factor receptors.…”
Section: Mirnas Regulate Nitrofen-induced Airway Smooth Muscle Cell Dmentioning
confidence: 99%
“…We report that rno-miR-3585-5p negatively alters two genes; BAZ2A and SIRPA; however, the exact mechanism is poorly understood. It has been shown that SIRPA, a member of the signalregulatory-protein family, can interact with surfactant proteins A and D to suppress alveolar phagocytosis without triggering an inflammatory response (41). This protein can be phosphorylated by tyrosine kinases and is found to participate in signal transduction triggered by CD47 and mediated by various growth factor receptors.…”
Section: Mirnas Regulate Nitrofen-induced Airway Smooth Muscle Cell Dmentioning
confidence: 99%
“…Further studies showed that SIRPα engagement through SP-A or SP-D lead to decreased uptake of apoptotic cells by alveolar cells. However during inflammation newly recruited macrophages escape this blocking and can then give efficient clearance of apoptotic cells [33]. This is an important concept as one is not be able to assume a receptor is available for ligand engagement just because of its presence.…”
Section: When Are Interactions Between Sirpα and Cd47 Functional? Effmentioning
confidence: 99%
“…The presence of two sialylated glycopeptides was consistent with the LC-MS analysis of reduced hCD99-Fc. The detected sialoglycopeptide APDGGFLDLSDALPDNENKKPT 41 AIPK contained Thr-41 and a Ser residue that potentially could be O-glycosylated. However, the exact site of O-glycosylation could not have been sequenced through the performed type of LC-MS experiment.…”
Section: Resultsmentioning
confidence: 99%